University’s Students’ Perceptions Of The Factors Influencing Their Willingness To Speak English - Virginia Gabrella Sengkey (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Adopting descriptive and comparative research designs, this study set out to determine the level of university students’ willingness to speak English in class, the factors shaping that willingness, and whether students differed in their perceptions of these factors according to gender and English class level. A total of 313 university students enrolled in various English classes took part in the study. The findings indicate that, as the students themselves perceived it, they were willing to speak English during lessons, and that the factors shaping this willingness were having an interesting topic to discuss, being confident that their answer was correct, and being familiar with the topic. Male and female students did not differ to any meaningful degree in how they perceived the factors that affected their willingness to speak English. Students at different English-class levels, however, differed in their perceptions of these factors.